2022
DOI: 10.21203/rs.3.rs-1269567/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cone Bioassays Provide Reproducible Bioefficacy Estimates with Different Anopheline Mosquitoes and Can Be Used for Quality Assurance of Pyrethroid Insecticide Treated Nets

Abstract: Background Quality assurance (QA) of insecticide-treated nets (ITNs) delivered to malaria-endemic countries is conducted by measuring physiochemical parameters, but not bioefficacy against malaria mosquitoes. The cone bioassay provides a simple evaluation of ITN bioefficacy and its conditions and parameters are prescribed by the World Health Organization (WHO). This study explored utility of cone bioassays for pre-delivery QA of pyrethroid ITNs in two test facilities using different mosquito species to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was also suspected that the mosquito strain that we had used (a pyrethroid susceptible strain of Anopheles farauti ) or technicalities related to conducting WHO cone bioassays at the PNG Institute of Medical Research were responsible for the observed inferior performance. We ruled out these possibilities categorically, by conducting a multi-centre trial with the same nets that showed that our observations from PNG were reproducible in an African ‘Good Laboratory Practice’ accredited facility 10 .…”
Section: Main Textmentioning
confidence: 99%
“…It was also suspected that the mosquito strain that we had used (a pyrethroid susceptible strain of Anopheles farauti ) or technicalities related to conducting WHO cone bioassays at the PNG Institute of Medical Research were responsible for the observed inferior performance. We ruled out these possibilities categorically, by conducting a multi-centre trial with the same nets that showed that our observations from PNG were reproducible in an African ‘Good Laboratory Practice’ accredited facility 10 .…”
Section: Main Textmentioning
confidence: 99%
“…This is normal because when nets are washed or exposed to UV radiation (sun exposure), total active ingredient (AI) content decreases and once a threshold AI concentration is reached, 100% bioefficacy normally observed with fully susceptible strains in new and unwashed nets is not maintained. However, other studies have demonstrated that recently manufactured new and unused LLIN products may not be able to pass WHO cone bioassay performance criteria with susceptible mosquito colonies, even though their total AI content was determined to be adequate in predelivery inspections [7, 11]. This may be for different reasons including restricted bioavailability of AI on the net surface due to the nature of the LLIN coating, presence of AI in chemical or physical states that may be detrimental to its effectiveness (such as isomers with reduced potency or crystalline states that may reduce the uptake of AI by mosquitoes) [5, 6, 12, 13].…”
Section: Introductionmentioning
confidence: 99%